The The Adoption of Innovations in Land Processing Without Burning by the People in the City of Dumai - Ade Irma (Jurnal Agribisnis, 2019)
This research is based on the background of the custom of the people who still do land cultivation by burning. This happens because people assume that the technique of burning is cheaper and faster, but this technique has many negative impacts. The technique of processing land without combustion is a recommended technique to use because it is safer and environmentally friendly, but there are still many people who are reluctant to do so because the cost is very large. The purpose of this research is to find out the land management system that is commonly carried out by the community and analyze the process of adopting innovations in land processing without burning by the people in Dumai City. This research method uses survey and interview methods. Sampling using the snowballsampling method was 14 respondents. Based on the results of the study, the treatment system carried out by the people in Dumai City experienced a transition, from how to burn without burning. The level of adoption of non-roasted land processing innovations in Dumai City through the process of community knowledge, persuasion, adoption decisions, implementation, and confirmation with a medium category indicated by the score category of 3.30.